Impact of implementing an evidence‐based definition of enteral nutrition intolerance on nutrition delivery: A prospective, cross‐sectional cohort study. (21st December 2022) - Liauchonak, Siarhei; Hamilton, Susan; Franks, Jennifer D.; Callif, Charles; Akhondi‐Asl, Alireza; Ariagno, Katelyn; Mehta, Nilesh M.; Martinez, Enid E.
Abstract: Background: Enteral nutrition (EN) interruptions because of EN intolerance impede nutrient delivery. We aimed to examine whether revising the EN intolerance definition of an algorithm would decrease EN interruptions and improve nutrient delivery in critically ill children. Methods: We performed a cross‐sectional cohort study including patients who were admitted to our intensive care unit (ICU) for >24 h and received EN. The EN intolerance definition in our nutrition algorithm was modified to include two symptoms of EN intolerance. We compared time to 60% EN adequacy (EN delivered/EN prescribed x 100) and EN interruptions before and after this intervention. Results: We included 150 eligible patients, 78 and 72 patients in the preimplementation and postimplementation cohorts, respectively. There were no significant differences in demographics and clinical characteristics. The preimplementation and postimplementation cohorts achieved 60% EN adequacy 4 (2–5) days and 3 (2–5) days after ICU admission, respectively ( P = 0.59). The preimplementation cohort had a median of 1 (1–2) interruption per patient and the postimplementation cohort 2 (1–3; P = 0.08). The frequency of interruptions because of EN intolerance within the first 8 days of ICU admission was 17 in the preimplementation and 10 in the postimplementation cohorts. Conclusion: Modifying the EN intolerance definition of a nutrition algorithm did not change the time to 60% EN adequacy or total number of EN interruptions in critically ill children. EN intolerance and interruptions continue to limit nutrient delivery. Research on the best definition for EN intolerance and its effect on nutrition outcomes is needed.